A bibliometric analysis of myocardial ischemia/reperfusion injury from 2000 to 2023 - Wang, Yifei; Guo, Lijun; Zhang, Zhibo; Fu, Shuangqing; Huang, Pingping; Wang, Anzhu; Liu, Mi; Ma, Xiaochang (Frontiers in Cardiovascular Medicine, 2023)
Background: Myocardial ischemia/reperfusion injury (MIRI) refers to the more severe damage that occurs in the previously ischemic myocardium after a short-term interruption of myocardial blood supply followed by restoration of blood flow within a certain period of time. MIRI has become a major challenge affecting the therapeutic efficacy of cardiovascular surgery. Methods: A scientific literature search on MIRI-related papers published from 2000 to 2023 in the Web of Science Core Collection database was conducted. VOSviewer was used for bibliometric analysis to understand the scientific development and research hotspots in this field. Results: A total of 5,595 papers from 81 countries/regions, 3,840 research institutions, and 26,202 authors were included. China published the most papers, but the United States had the most significant influence. Harvard University was the leading research institution, and influential authors included Lefer David J., Hausenloy Derek J., Yellon Derek M., and others. All keywords can be divided into four different directions: risk factors, poor prognosis, mechanisms and cardioprotection. Conclusion: Research on MIRI is flourishing. It is necessary to conduct an in-depth investigation of the interaction between different mechanisms and multi-target therapy will be the focus and hotspot of MIRI research in the future.